2011
DOI: 10.2169/internalmedicine.50.5995
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Pulmonary Hypertension in a Patient with Early-onset Pulmonary Emphysema Treated with Specific Drugs for Pulmonary Arterial Hypertension

Abstract: Severe pulmonary hypertension in chronic obstructive pulmonary disease (COPD) is referred to as 'disproportionate' because the elevated pulmonary artery pressure does not match the degree of air flow limitation. We report a 41-year-old man presenting with early-onset pulmonary emphysema and pulmonary hypertension with a mean pressure of 74 mmHg. Continuous intravenous epoprostenol led to marked hemodynamic improvement, and epoprostenol was successfully replaced with bosentan. The patient has been followed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Early studies of the effects of intravenous prostaglandin E1 (PGE1) observed decreases in pulmonary vascular resistance with increased cardiac output but were associated with worsened V/Q mismatch and increased hypoxemia [110]. In a recent case study Shimizu et al [111] reported significant haemodynamic improvement in a patient with disproportionate PH using long-term intravenous infusion of epoprostenol for over 3 years. A more recent study in patients with advanced IPF and PH showed that PH-targeted therapy with trepostinil may improve right heart haemodynamics and echocardiographic function without affecting systemic oxygen saturation [112].…”
Section: Treatmentmentioning
confidence: 99%
“…Early studies of the effects of intravenous prostaglandin E1 (PGE1) observed decreases in pulmonary vascular resistance with increased cardiac output but were associated with worsened V/Q mismatch and increased hypoxemia [110]. In a recent case study Shimizu et al [111] reported significant haemodynamic improvement in a patient with disproportionate PH using long-term intravenous infusion of epoprostenol for over 3 years. A more recent study in patients with advanced IPF and PH showed that PH-targeted therapy with trepostinil may improve right heart haemodynamics and echocardiographic function without affecting systemic oxygen saturation [112].…”
Section: Treatmentmentioning
confidence: 99%
“…An early small trial of prostacyclin in COPD patients in acute respiratory failure did not demonstrate improvement [83], but animal models have suggested that prostacyclin may have a protective effect in development of pulmonary hypertension in COPD [84]. Additionally, there has been a case-report of prostacycline being used in a COPD patient to treat disproportionate PH [85]. A clinical trial of Bosentan, an endothelin antagonist FDA approved for treatment of pulmonary arterial hypertension, did not show improvement in hemodynamics, functional capacity or quality of life [86].…”
Section: Treatment Of Pulmonary Vascular Disease In Copdmentioning
confidence: 99%
“…A favorable response to IV EPO was cited in a single case report of a 40-year-old male with emphysema and "out of proportion" PH. 260 Acute inhalation of iloprost in PH-COPD patients may improve exercise capacity and CPET parameters while preserving gas exchange. 261 However, this form of therapy is exceptionally expensive and long-term benefit has not been established.…”
Section: Treatment Of Ph In Copdmentioning
confidence: 99%